Platelet microbicidal protein alone and in combination with antibiotics reduces Staphylococcus aureus adherence to platelets in vitro. - Yeaman, M R (1994)
Bacterial adherence to platelets on the cardiac valve surface is believed to be critical in the induction of infective endocarditis. Recent studies have confirmed that thrombin-activated platelets secrete platelet microbicidal protein (PMP), which can both kill and exert nonlethal antiadherence effects against endovascular pathogens. In the present study, we quantified the influence of antibiotic and/or PMP exposures on in vitro platelet adherence of two Staphylococcus aureus strains, identical by DNA restriction and cell wall protein profiles, that differed in their susceptibility to PMP-induced killing (PMPs or PMPr, respectively). Adherence assays were performed by flow cytometry in the presence of sublethal PMP concentrations (1 to 2.5 micrograms/ml) alone or in combination with ampicillin (AMP) alone, sulbactam (SUL) alone, or AMP plus SUL (AMP-SUL), at levels achievable in serum. Exposure of the PMPs and PMPr S. aureus strains to antibiotics (for 2 h at 37 degrees C) prior to flow cytometry resulted in no substantive changes in the percent adherence to platelets compared with that for S. aureus cells not exposed to antibiotics, except for modestly increased adherence of both PMPs and PMPr cells exposed to AMP-SUL (18.5 and 15.8% increases, respectively). Addition of PMP to antibiotic-S. aureus mixtures (final 30 min) caused a significant decrease in S. aureus adherence to platelets, for both the PMPs and PMPr S. aureus strains, compared with antibiotic exposure alone (e.g., reduction in platelet adherence from 57.9 +/- 8.2% to 12.2 +/- 3.6% for PMPs cells exposed to AMP-SUL and PMP [P = 0.01]). Moreover, addition of PMP following exposure of the PMPs and PMPr strains to AMP-SUL reversed the enhanced bacterium-platelet adherence observed with such antibiotic exposures alone (P < or = 0.005). These data demonstrate that PMP exerts a potent antiplatelet adherence effect which is independent of its microbicidal capacity, rendering S. aureus cells less adherent to platelets in the presence or absence of antibiotics. Reduction of microbial adherence to platelets by PMP alone or with antibiotics provides further insight into the mechanism(s) that may be involved in host defense and antibiotic prophylaxis of infective endocarditis and other endovascular infections.